Lehrkräftebildung in der Bedarfskrise Programme - Positionierungen - Empirie - Behrens, Dorthe; Forell, Matthias; Idel, Till-Sebastian; Pauling, Sven (Studien zur Professionsforschung und Lehrer:innenbildung, 2023)
Since the beginning of the 2010s, there has been a shortage of teachers in Germany, which is being responded to with various special measures of lateral and lateral entry to accelerate recruitment. The contributions collected in this conference volume provide insights into current research, evaluation and discussion on the development of teacher education and the teaching profession under the conditions of the current demand crisis. The perspective does not only focus on the narrower institutional context of teacher education, but also sheds light on the profile of lateral and lateral entrants, how they deal with the professional challenges and the implications this has for the situation in schools. (DIPF/Orig.)